Characterization of Ralstonia solanacearum Using Fourier Transform Infrared (FTIR) Spectroscopy - Ma'alifah, Nur; Aini, Luqman Qurata; Abadi, Abdul Latief; Prillianti, Kestrilia Rega; Prabowo, Matheus Randy (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2022)
Ralstonia solanacearum, the causal agent of bacterial wilt disease is worldwide in distribution, and results in serious economic losses, particularly in the tropics. Detection and characterization of microorganisms by Fourier transform infrared spectroscopy (FTIR) technique promises to be of great value because of the method’s inherent sensitivity, small sample size, rapidity, and simplicity. In this study, we used FTIR spectroscopy for the characterization of Ralstonia solanacearum. The bacteria were grown on Nutrient Agar (NA) at 28°C for 48 hours. The colonies of Ralstonia solanacearum on nutrient agar medium were smooth circular, raised, and dirty white. Cultures of bacteria were identified by molecular methods using PCR techniques. The DNA was amplified using a specific primer pair, 759f/760r (forward primer: 5'- GTCGCCGTCAACTCACTTTCC 3’, reverse primer: 5'-GTCGCCGTAGCAATGCGGAATCG-3’). The PCR produced a single band of 280 bp from the isolated DNA of cultured bacteria. Bacterial spectra were obtained in the wavenumber range of 4000–400 cm-1 using FTIR spectroscopy. The identification of cell wall constituents in region 3000–2800 cm-1, the proteinaceous structure of bacteria in region 1665–1200 cm-1, and the fingerprint of bacteria in region 1200-800 cm-1 are all part of the spectra analysis in this study. Absorption bands obtained from bacteria Ralstonia solanacearum samples associated with protein, phospholipids, nucleic acids, and carbohydrates appear in the bacterial IR absorption spectra.